The Importance of Private Sector Development in Conflict-Affected Countries - Bold, Chris (World Bank, Washington, DC, 2012)
Paul Collier estimates that 73 percent of the poorest billion people in the world live in countries affected by conflict. In this book 'The Bottom Billion,' conflict is the first of the 'traps' responsible for keeping the populations of some countries in poverty. The author argues that low or negative economic growth in a country dramatically increases the chance of conflict.